Imagining the Big from the Small – An Analysis of the Chinese Carbon Emission Trading System Pilot Programs - Wang, Yuzheng (Tufts Archival Research Center, 2020)
This thesis analyzed China’s ETS pilot project with the purpose of informing the design of the national market. The result indicates that each local government has taken innovative and solid steps toward building an ETS market. The diversity in market design and features demonstrated how local governments experimented with local characteristics. Despite the effort, the result also found that the ETS pilots were not mature enough after six years of development. The markets were volatile in terms of trading volume and price. Besides, the markets were also characterized by last-minute trading, signaling their lack of daily activity. The scale and coverage of the ETS pilots were also inadequate to influence the production and market of related goods. Learning from these limitations, though, the central government could improve the national ETS design accordingly. These improvements should include but not limited to, making a plan to gradually phase out overallocation and free allocation, reducing policy uncertainties, ensuring adequate coverage, and keep constructing and publishing the ETS related data.